Visible Infinity (London Journal of Research In Humanities and Social Sciences, 2024)
There can only ever have been, or that will ever continue to be one infinite visible physical condition that has endured, and will continue to endure eternally. The physicists’ contention that visible matter and invisible dark matter and empty space have somehow managed to coexist at the same time after the supposedly finite big bang explosive commencement of the universe billions of light years ago is utterly invalid. There could never have been any empty space. The visible  space bar on a visible keyboard does not add a space between visible words. Depressing it merely adds an extended contrast in hue between the letters of the words. There is no empty space between the stars and the planets. There is merely a contrast in visible physical appearance. As there are an infinite number of visible stars, there is no way they could be assembled in only finite types. There is no way that any two stars could be separated by billions of finite miles of empty space. All one has to do is look up at the night sky in order to visually verify that the glaring neon white stars are clearly in view seen against the stark contrast of the visible black sky.